Manipulative-Based Instructional Sequences in Mathematics for Students With Disabilities. (January 2022) - Bouck, Emily C.; Anderson, Rubia D.; Long, Holly; Sprick, Jessica
Manipulative-based instructional sequences—including both concrete and virtual manipulative instructional sequences—are evidence-based or research-based mathematical interventions for students with disabilities. However, as options for manipulative-based instructional sequences increase, educators need support in deciding the best approach. In this manuscript, we provide practical tips for educators to make decisions about selecting and implementing manipulative-based instructional sequences for students with disabilities. We present and discuss the following steps educators should take when preparing to use a manipulative-based instructional sequence: (a) determine resources, (b) know the student, (c) identify the targeted mathematics, (d) evaluate time constraints, and (c) decide upon the ultimate goal of learning.